Effect of Perceived Reputation and Service Quality on Accounting Information Systems that Moderate Purchase Decisions - Rachma Widyani; Ajeng Wijayanti (Publikasi Indonesia, 2022)
This study aims to examine the effect of perceived reputation and service quality on accounting information systems which are moderated by purchasing decisions. The method in this study is quantitative with data collection techniques through questionnaires, the population in this study is MSME actors in DKI Jakarta and the number of samples obtained is 289 respondents as sellers in e-commerce. The data processing method in this study uses Smart PLS software which is used for validity testing and reliability testing in hypothesis testing. From the results of hypothesis testing proves that there is a significant influence of perceived reputation on accounting information systems, there is no significant effect of service quality on accounting information systems, there is no significant effect of purchasing decisions on accounting information systems, then there is no significant effect from the perceived reputation of the accounting information system which is moderated by purchasing decisions, but there is an influence of service quality on the accounting information system which is moderated by purchasing decisions.